EFFECT OF SHADOWING ON INFORMATION SYSTEMS STUDENTS SPEAKING FLUENCY AT ROYAL UNIVERSITY - Cecep Maulana; Irianto (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aimed to investigate the effectiveness of the shadowing method in improving speaking fluency among Class SI 1D students in the Information Systems Department at Royal University. A quasi-experimental design was applied involving 27 students divided into an experimental and a control group. The experimental group received structured shadowing activities through guided audio repetition and pronunciation modeling, while the control group was taught using conventional speaking exercises. The findings showed a significant improvement in the experimental group, with a mean post-test score of 86 and a normalized gain of 0.65 (moderate–high), compared to the control group’s mean score of 70 and gain of 0.23 (low). An independent samples t-test confirmed a statistically significant difference between both groups (t = 10.12, p < 0.05). Classroom observations indicated increased confidence, reduced hesitation, and better speech continuity among students exposed to shadowing. The study concludes that the shadowing method is an effective and practical strategy for enhancing speaking fluency among university-level Information Systems students.